Mapping Research Trends in Mangrove Ecosystem Services and Industrial Applications - Kurniawan, Rudi; j.ezugwu, umezurike; Sulistyowati, Enik; Riyana, Iis; Hamidah, Nur (Assyfa Journal Scientific Essay, 2025)
This research aims to elucidate trends in research related to mangrove ecosystem services and their industrial applications, which are vital for supporting sustainable development aligned with SDG 13 (Climate Action) and SDG 15 (Life on Land). Through a bibliometric analysis of publications from 2015 to 2025, the study seeks to map the evolution of research, focusing on carbon absorption, coastal protection, and mangrove-based industrial biotechnology. The analysis reveals a marked increase in interest regarding the use of mangroves for climate change mitigation and sustainable industry development. It underscores the necessity for interdisciplinary collaboration to effectively bridge academic research with industrial applications, thereby maximizing the benefits of mangroves. Ultimately, while mangroves possess significant potential to support sustainable development goals, an integrated approach is essential to ensure their sustainable industrial application.